2019
DOI: 10.3390/genes11010009
|View full text |Cite
|
Sign up to set email alerts
|

Intraspecific Diversity in the Cold Stress Response of Transposable Elements in the Diatom Leptocylindrus aporus

Abstract: Transposable elements (TEs), activated as a response to unfavorable conditions, have been proposed to contribute to the generation of genetic and phenotypic diversity in diatoms. Here we explore the transcriptome of three warm water strains of the diatom Leptocylindrus aporus, and the possible involvement of TEs in their response to changing temperature conditions. At low temperature (13 • C) several stress response proteins were overexpressed, confirming low temperature to be unfavorable for L. aporus, while … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

4
16
0

Year Published

2020
2020
2022
2022

Publication Types

Select...
4
2
2

Relationship

2
6

Authors

Journals

citations
Cited by 18 publications
(20 citation statements)
references
References 90 publications
(110 reference statements)
4
16
0
Order By: Relevance
“…These results are in line with previous studies that have used genomic and transcriptomic approaches to characterize the thermal adaptations of Southern Ocean diatoms, demonstrating that cells may employ common stress mechanisms at both thermal extremes (Mock et al, 2017;Pargana et al, 2020). Growth of Fragilariopsis cylindrus under both thermal extremes (−2, +11 • C) revealed similarities in altered gene expression relative to ambient conditions, indicating that generic stress responses were potentially employed in both thermal environments (Mock et al, 2017), and in Leptocylindrus aporus, expression of heat shock proteins (HSPs) was upregulated in both high and low temperature incubations (Pargana et al, 2020). The production of HSPs is known to increase during growth above T opt (Rousch et al, 2004;Leung et al, 2017), and has been shown to be maximized as temperatures approach thermal maxima (T max ) (Low et al, 2018).…”
Section: Discussionsupporting
confidence: 91%
“…These results are in line with previous studies that have used genomic and transcriptomic approaches to characterize the thermal adaptations of Southern Ocean diatoms, demonstrating that cells may employ common stress mechanisms at both thermal extremes (Mock et al, 2017;Pargana et al, 2020). Growth of Fragilariopsis cylindrus under both thermal extremes (−2, +11 • C) revealed similarities in altered gene expression relative to ambient conditions, indicating that generic stress responses were potentially employed in both thermal environments (Mock et al, 2017), and in Leptocylindrus aporus, expression of heat shock proteins (HSPs) was upregulated in both high and low temperature incubations (Pargana et al, 2020). The production of HSPs is known to increase during growth above T opt (Rousch et al, 2004;Leung et al, 2017), and has been shown to be maximized as temperatures approach thermal maxima (T max ) (Low et al, 2018).…”
Section: Discussionsupporting
confidence: 91%
“…We therefore hypothesize that thermal stress experienced at heatwave temperatures acted to enhance growth both at low (-2.2, -0.4 o C) and high (7.6 o C) thermal extremes (Figure 3). This idea is in line with previous studies that have used genomic and transcriptomic approaches to characterise the thermal adaptations of diatoms to the Southern Ocean, demonstrating that common stress mechanisms can be employed at both thermal extremes (Mock et al, 2017, Pargana et al, 2020. Growth of Fragilariopsis cylindrus under both thermal extremes (-2, +11 o C) revealed similarities in altered gene expression relative to ambient conditions, indicating that generic stress responses were potentially employed in both thermal environments (Mock et al, 2017), and Leptocylindrus aporus cultured at high and low temperatures revealed that the expression of heat shock proteins were upregulated under both thermal regimes (Pargana et al, 2020).…”
Section: Discussionsupporting
confidence: 84%
“…This idea is in line with previous studies that have used genomic and transcriptomic approaches to characterise the thermal adaptations of diatoms to the Southern Ocean, demonstrating that common stress mechanisms can be employed at both thermal extremes (Mock et al, 2017, Pargana et al, 2020. Growth of Fragilariopsis cylindrus under both thermal extremes (-2, +11 o C) revealed similarities in altered gene expression relative to ambient conditions, indicating that generic stress responses were potentially employed in both thermal environments (Mock et al, 2017), and Leptocylindrus aporus cultured at high and low temperatures revealed that the expression of heat shock proteins were upregulated under both thermal regimes (Pargana et al, 2020). The production of HSPs is known to increase during growth above Topt (Leung et al, 2017, Rousch et al, 2004, and has been shown to be maximised as temperatures approach thermal maxima (Tmax) (Low et al, 2018).…”
Section: Discussionsupporting
confidence: 84%
“…As pCO 2 increases, Pt4 may reduce HCO − 3 acquisition more preferentially than other strains, which would save more energy consumed by CCMs. However, the strains used in this study have been transferred from their local natural environment to laboratory conditions for several decades, in which evolutionary processes do not cease to occur (Lakeman et al 2009;Pargana et al 2020). Therefore, to better explore strain-specific response to ocean acidification, molecular and physiological experiments in both laboratory and field should be conducted using more recently isolated strains in the future.…”
Section: Discussionmentioning
confidence: 99%